Towards Integrating Meta-Level Programming and Configuration Programming - Loques, Orlando; Leite, Julius; Lobosco, Marcelo; Sztajnberg, Alexandre (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1999)
Configuration Programming, based on Architecture Description Languages, and Meta-Level Programming are considered promising approaches in the software engineering field. This paper shows that there is an immediate correspondence between some key concepts of Configuration Programming and Meta-Level Programming and that some of the main issues to be solved for their deployment in real systems are quite similar. The main proposition is that the integration of both approaches in a single configuration programming framework can assist in putting into practice meta-level programming in order to achieve separation of concerns and improve software reuse.